The treatment of detainees and the "Global War on Terror": selected legal issues - Turns, David (Naval War College Newport, Rhode Island, 2008)
This article will address selected legal issues relating to the treatment of detainees in the context of the "Global War on Terror" as a "hook" on which to hang some ideas of more general application and significance about the international legal framework of the "war." Some general (i.e.,jus ad bellum) international law aspects of the parameters of that framework have already been debated in the literature/ but the perspective adopted herein is of more specialist focus inasmuch as it concentrates on the practical issue that should resonate in the mind of all coalition military and associated personnel since the disclosure of ill-treatment of detainees in the custody of US and British forces in Iraq at Abu Ghraib and elsewhere:3 namely, once suspects in the "War on Terror" are captured, in accordance with what rules and legal standards are they to be treated?